HUSNUZAN DALAM PERSPEKTIF AL-QUR’AN SERTA IMPLEMENTASINYA DALAM MEMAKNAI HIDUP - Mamluatur Rahmah (UIN Raden Mas Said Surakarta, 2021)
Problems in life are part of human life. Every human being will be confronted with life's problems ranging from family, work environment, and social circles. In reality, though, there were few who felt discouraged over an issue that remained unresolved and made him forget his own meaning and purpose in life to serve god. For that, husnuzan became necessary to rerecognize and apply to the knowledge that everything experienced in his life came from the almighty god. This article is for the purpose knowing hunsuzan in the perspective of the Qurâ€™an, inclucing husnuzan to Allah, Â Myself, others, and the circumstances and application of them in making a living. The kind of research used is heirloom studies with a descriptive method of analysis. The conclusions of this study include that Husnuzan can clear one's mind. With husnuzan, one is able to get rid of bad prejudices and re-awaken about the meaning of the events experienced, and can reassure the soul that is always shrouded in happiness, facilitated all affairs and elevated by Allah SWT.